FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM MENGGUNAKAN INTERNET BANKING - Eko Suyono (SEGMEN Jurnal Manajemen dan Bisnis, 2018)
The purpose of this study is to analyze effects of perceived of privacy protection, perceived of security protection, perceived of trust in online transactions, and perceived of risk and benefit on student's interest to use internet banking. By using purposive sampling, 60 students of Accounting Department of Jenderal Soedirman University were selected as sample. The results find that perceived of security protection, perceived of trust in online transactions, and perceived of risks and benefits have a significant positive effect on student interest in using internet banking. Moreover, perceived of privacy protection does not affect student interest in using internet banking. Keywords: perceived of privacy protection, perceived of security protection, perceived of trust in online transactions, perceived of risk and benefit, student's interest, internet banking